AN EMPIRICAL STUDY ON CONSUMERS BEHAVIOR TOWARDS GREEN PRODUCTS CONSUMPTION IN INDIA - Vijayasree, P N; Pavan Sathavalli, Dr. Mahesh; Prakash, Mr. C. (The journal of contemporary issues in business and government, 2022)
The spread of Novel Corona virus (COVID-19) has had far-reaching effects on the supply chain, from raw materials to final goods. Consequences for public health, hygiene, and diet have resulted from these shifts. Concerns about food safety have contributed to a growth in consumers' preference for buying and eating locally produced foods. During the COVID-19 pandemic, consumers considered green goods as safer and healthier, which might have long-term effects on their diets and healthcare spending. Concern for the environment has gone global. Marketers are aware of the need to embrace green marketing tactics in response to the World Health Organization's Sustainable Development Goals (SDGs. In addition, these days shoppers know a little more about green advertising than they did a year ago. As a result, several Indian factories are adopting eco-friendly advertising strategies. Using a self-administered survey, primary data was gathered for this investigation. In all, 400 replies met the criteria for further examination. Therefore, a new model is being presented to the marketers in order to increase their market share and profit among the rivals in the business.